Analysis of Difference in Microbial Community and Physicochemical Indices Between Surface and Central Parts of Chinese Special-Flavor Baijiu Daqu - Chen, Yanru; Li, Kaimin; Liu, Ting; Li, Ruyi; Fu, Guiming; Wan, Yin; Zheng, Fuping (Frontiers in Microbiology, 2021)
Special-flavor Baijiu is a unique Baijiu in Jiangxi Province, China, which uniqueness mainly depends on the unique production process of special-flavor Baijiu Daqu. However, the microbial structure and physicochemical indices of different parts of special-flavor Baijiu Daqu still remains unknown. This greatly reduces the actual value of Daqu in the production of special-flavor Baijiu. Therefore, culturing dependent and Illumina MiSeq sequencing methods were used to analyze the microbial structure of special-flavor Baijiu Daqu. The results indicated that Chinese special-flavor Baijiu Daqu have a complex microbial diversity. The predominant bacterial communities were Bacillales, Lactobacillales and Rhodospirillales, while Saccharomycetales and Eurotiales were the predominant fungal communities. The significant different microbial community and distribution were showed between the surface and central parts of Daqu. Acetobacter and Pichia genera were the predominant microbial in the surface part of Daqu, respectively, whereas Aspergilus, Kroppenstedtia, Oceanbacillus and Bacillus genera were the predominant microbial in the central part of Daqu. Meantime, the different microbial distribution between the surface and central parts of Daqu causing the significant difference in the physicochemical indices. These results can provide an important theoretical basis for improving the brewing process and the quality of special-flavor Baijiu.